The measurement of rate of passage using different pairs of alkane as markers for sheep fed hay or fresh grass - Kustantinah, Kustantinah; Mayes, R.W.; Orskov, E.R. (Faculty of Animal Science, Universitas Gadjah Mada, 2010)
This study used alkanes marker absorbed in the paper bung. Four pairs of alkanes: C30:C37, C18:C34, C26:C36 and C24:C38 were introduced to sheep by mouth, with a different time of dosing. The first group of sheep (n= 6) that were fed hay and second group of sheep (n = 4) were fed fresh ryegrass at similar dry matter intake (DMI), from the alkane marker excretion were calculated residence time of digesta in the digestive tract (mean retention time / MRT). MRT calculations were performed for each individual alkane on each individual sheep with two different feed. From the calculation, it was found that the MRT obtained in the group of sheep fed hay was 35.8 hours (C24), 43.0 hours (C76), 41.6 hours (C,8), 40.1 hours (C30), 40.8 hours (C32), 42.0 hours (C34), 48.0 hours (C36), and 40.3 hours (C38). In the group sheep fed fresh ryegrass, the estimated MRT was 32.2 hours (C24), 41.7 hours (C26), 36.3 hours (C28), 40.3 hours (C30), 40.9 hours (C32), 36.6 hours (C34), 45.2 hours (C36), and 34.5 hours (C38). It can be seen that in general the value of MRT for sheep fed hay gave a higher value when compared with the MRT in the group fed fresh ryegrass, although statistically the MRT of the two groups did not differ significantly, except for MRT estimated using marker C38. MRT which estimated using the C38 gave a significant difference (P <0.05), i.e. 40.3 hours in sheep fed hay and 34.5 hours in sheep fed fresh ryegrass. The results of observations made, indicated that, for all types of markers and in all groups of sheep, in general there was no significant differences between MRT, except for C,4vsC36 (P<0.05) for groups of sheep fed hay and for C24vsC36, and C33vsC36 (P<0.05) for the group of sheep fed fresh ryegrass. The use of these alkanes markers were absorbed in paper bung provides a good estimation of the MRT.